Ferroptosis: A Critical Moderator in the Life Cycle of Immune Cells - Wang, Ping; Lu, Yuan-Qiang (Frontiers in Immunology, 2022)
Ferroptosis is a form of programmed cell death that was only recognized in 2012. Until recently, numerous researchers have turned their attention to the mechanism and function of ferroptosis. A large number of studies have shown potential links between cell ferroptosis and infection, inflammation, and tumor. At the same time, immune cells are vital players in these above-mentioned processes. To date, there is no comprehensive literature review to summarize the relationship between ferroptosis and immune cells. Therefore, it is of great significance to explore the functional relationship between the two. This review will attempt to explain the link between ferroptosis and various immune cells, as well as determine the role ferroptosis plays in infection, inflammation, and malignancies. From this, we may find the potential therapeutic targets of these diseases.